Travellers’ perspectives on historic squares and railway stations in Italian heritage cities revealed through sentiment analysis - Stellacci, S.; Moro, S. (Journal of Urban Design, 2023)
This study undertakes sentiment analysis of online reviews of public exterior spaces – historic squares and railway stations – in popular destinations in Italy, with the aim of offering new perspectives of community engagement in urban design analysis. The experience of walking through urban spaces in Italian heritage cities is evaluated under indicators of place quality and connectivity, i.e., aesthetic perception, social interaction, body mobility, facilities and amenities, sense of safety, and destination loyalty. Such advanced analysis can reshape the way we interpret the thoughts and emotions of wider communities so that these are included in local place-focused development strategies.